Abnormal Expression of Type 1 Plasminogen Activator Inhibitor and Tissue Factor in Severe Preeclampsia - Estellés, Amparo; Gilabert, Juan; Grancha, Salvador; Yamamoto, Koji; Thinnes, Terri; España, Francisco; Aznar, Justo; Loskutoff, David (Thrombosis and Haemostasis, 1998)
Preeclampsia is a multisystemic obstetric disease of unknown etiology that is commonly associated with fibrin deposition, occlusive lesions in placental vasculature, and intrauterine fetal growth retardation. We previously reported that type 1 plasminogen activator inhibitor (PAI-1) levels are significantly increased in plasma and placenta from pregnant women with preeclampsia compared to normal pregnant women. In the present report we localize the expression of placental PAI-1 in greater detail and compare it with that of tissue factor (TF), a procoagulant molecule, and vitronectin (Vn), a PAI-1 cofactor. We also examine the expression of two cytokines, tumor necrosis factor α (TNFα) and interleukin-1 (IL-1), in order to begin to define the underlying mechanisms responsible for the elevated levels of PAI-1 and fibrin deposits observed in placenta from preeclampsia. We demonstrate a significant increase in PAI-1, TF and TNFα antigen and PAI-1 and TF mRNA in placentas from preeclamptic patients. PAI-1 mRNA was increased not only in syncytiotrophoblast and infarction areas, but also in fibroblasts and in some endothelial cells of fetal vessels in placentas from preeclamptic patients. However, there was no colocalization between PAI-1, TF, Vn and TNFα in placental villi. The elevated TNFα in the placenta may induce PAI-1 and TF, and thus promote the thrombotic alterations associated with preeclampsia.